Snake and Ladder Game to Improve Students' Mastery of Arabic Vocabulary: Media Ular Tangga untuk Meningkatkan Penguasaan Mufrodat Bahasa Arab Siswa - Pulangsih, Wiku; Arifin, Moch. Bahak Udin By (Indonesian Journal of Education Methods Development, 2025)
General background: Vocabulary mastery is a key element in learning Arabic, as it supports students’ overall language skills and comprehension. Specific background: In many schools, including SMP Muhammadiyah 6 Krian, Arabic vocabulary learning is still dominated by conventional media such as textbooks and whiteboards, which often fail to stimulate student interest. Knowledge gap: Limited research has explored the integration of traditional games as structured learning media for Arabic vocabulary at the junior high school level. Aims: This study aims to develop a snake and ladder game as a learning medium to improve students’ mastery of Arabic vocabulary (mufrodat). Results: Using the Borg and Gall R&D model (9 stages), data were collected via observation, interviews, and questionnaires. The media validation score was 84.4%, language validation 100%, and material validation 85.7%, all categorized as highly feasible. Student response reached 90.4%, also in the highly feasible category. Novelty: The study transforms a familiar traditional game into a structured, curriculum-based Arabic learning medium. Implications: This media can be an engaging alternative to foster active learning and motivation in Arabic classes. Highlights : Combines traditional games with curriculum-based Arabic learning Achieves high validation scores from experts and students Offers engaging media to support active vocabulary learning Keywords : Arabic Vocabulary, Snake and Ladder, Learning Media, Junior High School, R&D Model